Implementasi Kebijakan Sertifikasi Guru dalam Rangka Meningkatkan Profesionalitas Guru di Kota Yogyakarta - Bachtiar Dwi Kurniawan (Jurnal Studi Pemerintahan, 2011)
This research was conducted to determine teacher certification policies, especially the line of portofolio, in order to improve profesionalism teachers. Research certification policy implementation especially want to see how far the process of implementation conducted by the executive, and what factors influence teacher certification policy implementation in Kota Yogyakarta. Further research is intended to see the impact of teacher certification policy toward teacher professionalism in teaching and learning. This research was conducted using qualitative methods with descriptive approach. This study found several things, including: first, in terms of teacher certification process of policy implementation in both the City Department of Education and LPTKs can be said to run well and smoothly, just have a little problem, both are experiencing problems related to the limited facilities and supporting infrastructure. It happened because the central government did not allocate budget to support the implementation of the program. Second, in terms of policy impact, there has been no increase in certified teachers' professionalism significantly. The attitude of teachers in conducting certification policy is only visible when pursuing welfare only, while the quality of teaching received less attention.